Identification of a New Coronavirus in Rectal Swabs: A Novel Perspectives - Anna Liskova; Vladimir Zajac (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Each and every virus is a parasite that depends entirely on its host to survive. This is the fundamental prerequisite for its existence. Although it is generally accepted that the virus can exist without a carrier for 2 to 5 seconds before it spreads to another species, the parasite must have its host and is therefore a living cell. It is difficult to follow these viral pathways, and the available research is incomplete. However, this is a crucial issue that has the potential to cause a significant paradigm shift in how we view viruses. The primary carrier, however, cannot be host organ cells because they could easily damage them. In terms of the mechanism of existence and transmission, the following could be the most suitable carriers of the virus: bacteria, yeast or other single-cell organisms. Based on our long-term study of BLV and HIV, we conclude that the carriers of these viruses are bacteria or yeast. Viruses can exist in these carriers for months or years. Carriers do not mind at all that the virus multiplies and mutates in them. The coronavirus has been found in the stools of infected people in several laboratories, which has been explained by the body cleansing itself of the virus. However, this is not the case. The virus can leave the body, but based on our results in the HIV system, it usually remains in the intestinal and respiratory tract of the carrier, where it can exist for a long time. So far, no one but us has detected the presence of the virus in the intestinal tract for 15-25 days, after infection. This is a very significant finding that can help resolve some of the espects of the new coronavirus epidemic.